2014
DOI: 10.2134/agronj14.0316
|View full text |Cite
|
Sign up to set email alerts
|

Malt Barley Cultivar Ranking under Long‐Term Tillage Systems in a Semiarid Region

Abstract: Malt barley (Hordeum vulgare L.) production is shifting in the Great Plains from conventional clean-tillage (CT) methods to reduced tillage (RT) and no tillage (NT). This study aimed to determine the effect of tillage on the relative ranking of malt barley cultivars for yield components, grain yield, and quality. Six barley cultivars were grown in southwestern North Dakota from 2010 through 2013 under long-term CT, RT, and NT. Ranking of cultivars did not change across tillage systems for plant density, plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Tillage had no effect on grain yield in all years, but continuous barley reduced yield compared with barley–pea in 2011 (Table 5). Several researchers (Sainju et al, 2013; Carr et al, 2014) reported that tillage had no effect on Tradition cultivar of malt barley grain yield in eastern Montana and southwestern North Dakota. It was surprising that irrigation did not significantly increase grain yield compared with no‐irrigation in all years (Table 5), except during the below‐average precipitation in 2008, suggesting that irrigation is needed to sustain yield during extended dry periods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tillage had no effect on grain yield in all years, but continuous barley reduced yield compared with barley–pea in 2011 (Table 5). Several researchers (Sainju et al, 2013; Carr et al, 2014) reported that tillage had no effect on Tradition cultivar of malt barley grain yield in eastern Montana and southwestern North Dakota. It was surprising that irrigation did not significantly increase grain yield compared with no‐irrigation in all years (Table 5), except during the below‐average precipitation in 2008, suggesting that irrigation is needed to sustain yield during extended dry periods.…”
Section: Resultsmentioning
confidence: 99%
“…A possible reason could be lower N availability at the surface layer with no‐till than conventional till, as soil NO 3 content at 5 to 10 cm was lower with no‐till than conventional till (Sainju et al, 2014c). Carr et al (2014) reported that malt barley protein concentration increased as tillage intensity increased. No‐till management can be a viable option to sustain malt barley quality by reducing protein concentration of grain for malting purposes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All tillage plots in each of the eight blocks were seeded uniformly to spring wheat in 2006 and 2007, field pea in 2008, and corn ( Zea mays L.) in 2009 to eliminate previous crop treatment effects. In the current study, barley ( Hordeum vulgare L.) was seeded in tillage plots in four blocks and rotated with corn seeded in tillage plots in the other four blocks from 2010 through 2013 (Carr et al, 2014). Soil organic matter (SOM) concentration in the top 15‐cm (6‐in) of soil was determined by compositing 9 to 10, 2.5‐cm (1‐in) diameter soil cores randomly collected using a hydraulic‐driven soil probe in each of two fields before establishing tillage whole plots in 1992 by loss‐on‐ignition.…”
Section: Methodsmentioning
confidence: 99%
“…Three 6‐row (Lacey, Stellar‐ND, and Tradition) and three 2‐row (Conlon, Conrad, and Pinnacle) barley cultivars were seeded at 27 live kernels/ft 2 in the interior seven rows using a low‐disturbance, nine‐row small‐plot seeder with fluted‐disk openers directly into NT plots where canola, corn, pea, and spring wheat stubble remained after harvest the previous year. The barley cultivars are all malt types, have a range of growth characteristics and other traits (Ransom et al, 2013), and were the most widely grown barley cultivars in the state during the study (Carr et al, 2014).…”
Section: Useful Conversionsmentioning
confidence: 99%